2008
DOI: 10.1093/fampra/cmn013
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of research data by GPs: a cautionary tale for primary care researchers

Abstract: We found that when GPs were asked to record basic clinical information, for the purposes of a primary care-based study, there was a significant level of inaccurate reporting. The results from our study confirm the importance of quality control in primary care research, especially in studies that involve GPs' reporting data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Using electronic coded primary care data will not only help healthcare providers in the development of clinical decision support systems and surveillance systems but also provide the platform for primary care researchers to conduct evidence-based research (Gormley et al, 2008;Patel et al, 2005;Smith et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using electronic coded primary care data will not only help healthcare providers in the development of clinical decision support systems and surveillance systems but also provide the platform for primary care researchers to conduct evidence-based research (Gormley et al, 2008;Patel et al, 2005;Smith et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The use of healthcare information systems to record primary care clinical data is significantly variable among general practitioners (GPs) (S. Rollason, Khunti, & de Lusignan, 2009). In a study conducted in the UK to examine the accuracy of primary care data reporting by GPs, Gormley et al (2008) found that "when GPs were asked to record basic clinical information, for the purposes of a primary care-based study, there was a significant level of inaccurate reporting" (p. 209). This variability could be attributed to lack of interoperable standards and no standardized approach to recording clinical encounters in information systems at the primary care level.…”
Section: Introductionmentioning
confidence: 99%